Krisis Efektivitas Bimbingan dan Konseling di Sekolah: Ketika Konselor Menjadi Generalis Tanpa Spesialis : The Crisis of Effectiveness of Guidance and Counseling in Schools: When Counselors Become Generalists without Specialization - Astrid Apandi; Aswar, Aswar (TARBIYAH: Jurnal Pendidikan dan Pembelajaran, 2025)
The effectiveness of Guidance and Counseling services in schools has become an important topic of discussion as the complexity of student problems increases. One emerging issue is the tendency for counselors to act as generalists without specialization, potentially weakening the impact of guidance and counseling services on students' academic, social, and emotional development. This article aims to examine the crisis in guidance and counseling effectiveness when counselors act as generalists and to identify opportunities to strengthen guidance and counselling services through counselor specialization. This research uses a literature review approach by reviewing national journals published in the last five years that are relevant to the field of guidance and counseling. Data were analyzed using thematic analysis to identify patterns of findings related to the causes, impacts, and implications of the generalist role in guidance and counseling services. The results of the study indicate that general guidance and counseling services tend to be administrative, lack depth, and are not well-targeted, resulting in an insignificant impact on student development. In conclusion, strengthening guidance and counselling effectiveness requires counselors with clear competencies and specializations so that guidance and counselling services can make a real contribution to student development.